Assessment of Factors Affecting Willingness To Pay/Accept: A Study From Begnas Watershed, Nepal - Poudel, Sanjay; Bhattarai, Suman; Regmi, Siddhartha; Gautam, Deepak (International Journal of Environment, 2021)
This study prioritized five major ecosystem services from the watershed which included clean and silt less water, conservation and biodiversity, fresh environment, tourism, and beautiful landscape. Among these ecosystem services, the fresh environment was ranked first based on respondent’s importance. We conducted multiple focus group discussions, key informant surveys, a household survey, and performed statistical analysis to derive results. About 120 respondents were surveyed, out of which 60 were from upstream and 60 were from the downstream community. The majority of the respondents agreed to participate in the PES mechanism for the conservation of watersheds. The present study has estimated average WTP NRs 114.51/ropani/year/HH and WTA of NRs118.18/ropani/year/HH for conservation of watershed. The probit model was adopted to identify the factors affecting people to pay or accept for ecosystem services. Respondent’s socio-economic characteristics such as gender (female), household income, higher education level, and people involved in agriculture and tourism had a positive impact on willingness to pay in downstream community, while the variables occupation (agriculture and tourism) and property size only had a positive relationship with a willingness to accept in upstream community. Our findings showed the feasibility to initiate and implement the PES mechanism in this watershed and the result of this study could also be used to design a long-term wetland management plan in the future to preserve the wetland. Moreover, time and again studies on the monetary values for ecosystem services are also recommended to assess the varying behavior of the people with time and development.